The Unified Support-Engineering Flywheel: Data, AI and Shared Metrics to Maximize CSAT - Mukul Garg, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article introduces the Unified Support-Engineering Flywheel, a framework integrating data engineering, artificial intelligence (AI), and shared key performance indicators (KPIs) to dismantle organizational silos between support and engineering teams. By unifying support metrics (First Contact Resolution [FCR], Resolution Time), engineering metrics (Mean Time to Repair [MTTR], Log Error Rates), and Customer Satisfaction (CSAT) within a data lakehouse/mesh architecture, organizations can leverage AI-driven root cause analysis to proactively address systemic customer experience (CX) issues. Case studies demonstrate 25–40% improvements in CSAT within 6 months of implementation. The flywheel’s self-reinforcing cycle—where shared data enables faster issue resolution, improving CX and generating higher-quality data—proves critical for aligning cross-functional goals and maximizing customer satisfaction.
Keywords: support engineering integration; customer satisfaction (CSAT); root cause analysis (RCA); data lakehouse; AI-driven operations; cross-functional KPIs; CX Impact Score